Effect of Silicon Application Methods on Drought Tolerance, Growth and Yield of Some Varieties of Vigna unguiculata (L.) Walp in Gombe State (Asian Journal of Plant Biology, 2023)
One of the things that limits crop yield is drought. It has been demonstrated that silicon (Si) plays a significant part in reducing environmental stress in cowpea. To investigate the impact of silicon (Si) on plant development, drought tolerance, physiology, and anatomy, the cowpea white variety and cowpea brown variety were chosen. Two cowpea types were sown in each pot during the trial, which was carried out in August 2021 at Gombe State university. Four treatments—a zero treatment, silicon (Na2SiO3) in soil, silicon (Na2SiO3) in seed, and silicon (Na2SiO3) in water—were used in the experiment, which was set up in a completely randomized block design. Vegetative, physiological, and reproductive factors are among those measured. The cowpea white treatment's findings for the vegetative parameters include the greatest averages for plant height (17.2), leaf count (14), stem diameter (1.9), and trifolium count. The greatest chlorophyll concentration of any treated silicon variety found in seed is 0.68, while the highest chlorophyll stability index of any variety found in soil is 50% for the cowpea white variation. Cowpea white of the treatment silicon in seed has the lowest transpiration rate of 0.1 mL, whereas cowpea white and brown of the treatment silicon in soil have the highest relative water contents (91.4% and 89.7%, respectively). The cowpea brown treatment silicon seed's reproductive properties had the highest mean flower count (3.7), compared to the white type, there were 1.7 pods, 17.1 pods, 5.7 pods, 12.0 seeds per pod, and 49g of total biomass. The cowpea white variety benefits from the Na2SiO3's effects on physiology and vegetative parameters, whereas the brown variations benefit from it in terms of reproduction.
Keywords: Silicon; Drought Stress; Physiology; Vegetative; Cowpea